Global talent management during times of uncertainty - Schlosser, Francine; McPhee, Deborah M. (Talent management (Emerald Publishing), 2022)
HRM practitioners and academics have been blindsided by unprecedented changes in the global war on talent. In response, Global Talent Management During Times of Uncertainty offers a multi-disciplinary perspective that identifies emerging global issues and new strategic and research approaches. This volume explores uncertain contexts related to socio-political and socio-economic change. Chapters investigate how rapidly evolving national policies and social and cultural contexts influence the attraction, management, and retention of mobile talent, and consider how such uncertainty may continue to affect post-pandemic global talent management (GTM). Manuscripts in this global volume touch on diverse cultural and geographic contexts, including Canada, the United States, Brazil, Russia, the Ukraine, Norway, Denmark, China, New Zealand, and the United Kingdom. Authors highlight how GTM is influenced by disinformation, cultural differences, and multiple business environments. Scholars identify the importance of cross-disciplinary talent strategies involving military leadership principles when facing uncertainty caused by macro events. GTM practices may not work effectively in a local context but political city initiatives provide avenues for shared regional talent strategies. We delve into perspectives of sustainability, including: the loss of highly skilled workers to more developed countries, the underutilization of skilled immigrants, the retention of post-pandemic healthcare workers, the cultural differences leading to misunderstanding of justice perceptions, and the lasting effects of war and the pandemic on GTM.